The influence of «cross-subvention» on economic efficiency of thermal insulation of buildings - Muzychak, Andriy; Voznyakovska, Olya (Lviv Polytechnic Publishing House, 2015)
Influence of «cross-subvention» on economic efficiency thermal insulation of buildings is viewed. The optimum thickness of thermal insulation for each tariff group is calculated. Awarded the negative role of the modern tariff policy. It is shown that to improve the attractiveness of the energy efficiency measures required state participation. The proportion of state compensation must be up to the «crosssubvention».
Keywords: heating; tariffs; cross-subvention; thermal insulation; economic thickness